Delayed intravenous immunoglobulin treatment increased the risk of coronary artery lesions in children with Kawasaki disease at different status. Issue 4 (19th May 2018) - Qiu, Huixian; He, Yuee; Rong, Xing; Ren, Yue; Pan, Lulu; Chu, Maoping; Wu, Rongzhou; Shi, Hongying
ABSTRACT: Objective : Kawasaki disease (KD) is a systemic vasculitis with serious complications, especially the development of coronary artery lesions (CALs). The aim of this study was to identify the risk for the development of CALs with IVIG treatment of KD >10 days after illness onset in patients with different KD status, and explore potential moderators of the association between delayed treatment and CALs. Methods : We performed a retrospective review of the medical records of KD patients. All patients were divided into two groups (conventional therapy group and delayed therapy group, IVIG treatment ≤10 days vs >10 days). We compared the demographic and clinical characteristics, laboratory data, and analyzed risk factors for CALs in patients who received IVIG treatment >10 days, and determined whether different status of KD modified the effects of delayed IVIG treatment on CALs. Results : In the delayed IVIG treatment group, children were more likely to develop CALs and the proportion of incomplete KD was higher, compared with the conventional therapy group. The number of children younger than 12 months or older than 61 months was higher and children had higher BMI and were more likely to receive steroids before diagnosis in the delayed IVIG treatment group compared with the conventional therapy group. Delayed IVIG treatment was an independent risk factor for the development of CALs (adjusted OR = 2.90, 95%CI = 1.42, 5.91). Delayed therapy children with higher levels of C-reactive protein (>79 mg/L) and erythrocyte sedimentation rate (>34 mm/h) had the highest risk for developing CALs (OR = 5.68, 95%CI: 1.17, 27.59; OR = 4.11, 95%CI: 1.62, 10.46, respectively). Conclusion : Delayed IVIG treatment was an independent risk factor for the development of CALs. Children in the delayed IVIG treatment group with higher levels of CRP and ESR (CRP >79 mg/L, ESR >34 mm/h) had the greatest likelihood of developing CALs.